2008
DOI: 10.1177/1753425907087257
|View full text |Cite
|
Sign up to set email alerts
|

Structural investigations into the interaction of hemoglobin and part structures with bacterial endotoxins

Abstract: An understanding of details of the interaction mechanisms of bacterial endotoxins (lipopolysaccharide, LPS) with the oxygen transport protein hemoglobin is still lacking, despite its high biological relevance. Here, a biophysical investigation into the endotoxin:hemoglobin interaction is presented which comprises the use of various rough mutant LPS as well as free lipid A; in addition to the complete hemoglobin molecule from fetal sheep extract, also the partial structure α-chain and the heme-free sample are s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…␣ and ␤ Subunits of Human Hb Harbor LPS Binding SitesPrevious studies have shown that tetrameric Hb from various species, as well as the ␣ subunit of sheep Hb, can bind bacterial LPS (18). Here, we examined whether the isolated subunits of human Hb could also bind LPS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…␣ and ␤ Subunits of Human Hb Harbor LPS Binding SitesPrevious studies have shown that tetrameric Hb from various species, as well as the ␣ subunit of sheep Hb, can bind bacterial LPS (18). Here, we examined whether the isolated subunits of human Hb could also bind LPS.…”
Section: Resultsmentioning
confidence: 99%
“…The invertebrate respiratory protein, hemocyanin, which is a functional homologue of Hb also binds LPS (12)(13)(14), indicating the evolutionary significance of such interactions. Previous studies have characterized the interactions of Hb and LPS through biophysical methods such as isothermal titration calorimetry and Fouriertransform infrared spectroscopy (17,18), which suggested that Hb intercalates into and alters the aggregate structure of LPS polymers, transitioning it from a relatively dormant multilamellar structure to a bioactive cubic structure. It has been shown that Hb interacts predominantly with the acyl chains and phosphate moieties of lipid A (20).…”
Section: Hemoglobin (Hb) Functions As a Frontline Defense Molecule Dumentioning
confidence: 99%
“…Previously it was shown that Hb causes a disaggregation of LPS Re structures [17]. To continue the examination of this phenomenon we applied freeze-fracture electron microscopy to examine whether this represents a general behaviour.…”
Section: Resultsmentioning
confidence: 99%
“…The measurements were done as recently described [17]. Briefly, a small amount of the samples was sandwiched between two copper profiles as used for the double-replica technique and frozen by plunging the sandwiches immediately into liquefied ethane-propane-mixture cooled in liquid nitrogen.…”
Section: Freeze-fracture Electron Microscopymentioning
confidence: 99%
“…Amino acid sequence homology of RVFHb␣P was used for the selection of the template. Two main criteria were included during the selection of template: (i) the selected protein should possess an authenticated crystal structure and (ii) the template must demonstrate maximum homology with the RVFHb␣P amino acid sequence (14). After selecting the template based on the above criteria, its crystal structure was used to model the structure of RVFHb␣P.…”
Section: Cell Lines and Transfection (I) Human Vaginal Epithelial Cementioning
confidence: 99%